Two Little Witches : A Halloween Counting Story - Harriet Ziefert (Singapore Candlewick Press, 1998)
It's Halloween night and the trick-or-treaters are making their rounds. One little witch meets one little witch and then they're joined by a plump pumpkin and a fuzzy bunny, a friendly pirate and a pink princess until ten trick-or-treaters tiptoe together up to a dark scary house and ... a MONSTER opens the door! Oh, no! Ten trick-or-treaters run home as quickly as they can.
Keywords: Read Aloud -- Read Aloud